2018
DOI: 10.1590/s0004-2803.201800000-41
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intestinal Secretagogues for Chronic Constipation: A Systematic Review and Meta-Analysis

Abstract: Intestinal secretagogues are useful and safe therapeutic alternatives for the treatment of constipation-related syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The literature search yielded 766 records. In total, 31 MAs 939 met the eligibility criteria (Figure 1). MAs of head-to-head trials were unavailable, hence we included network MAs presenting evidence from indirect comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 766 records. In total, 31 MAs 939 met the eligibility criteria (Figure 1). MAs of head-to-head trials were unavailable, hence we included network MAs presenting evidence from indirect comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Superiority of tenapanor versus placebo has been established in three double-blind, placebo-controlled trials and reviewed in multiple systematic reviews and meta-analyses [15,[70][71][72][73]. In the pivotal trials T3MPO-1 and T3MPO-2, tenapanor demonstrated statistically significant improvement over placebo in the FDA-guidance composite endpoint, as well as in each of the individual symptoms, at the 6/12, 9/12, and 13/26-week time points (except CSBMs at the 6/12 time point in T3MPO-1) [9,69,71,72].…”
Section: Tenapanormentioning
confidence: 99%
“…Trials studying different doses of a single treatment (e.g., 16,32, and 48 μg lubiprostone; 1, 2, and 4 mg prucalopride; and 0.5 and 1 mg alvimopan) or non-approved treatment dosages (e.g., linaclotide 1000 μg) were included in the treatment network. In general, different doses of a single treatment were considered as separate treatment modalities in the network.…”
Section: Network Meta-analysismentioning
confidence: 99%
“…In clinical practice, selection of the most appropriate therapy for CC is challenging due to the lack of direct comparisons between the available constipation drugs. Most published trials on constipation treatments are placebo-controlled studies, limiting the ability to compare active treatments [15,16]. A valid statistical estimate of the comparative efficacy of different treatment modalities can be achieved using a network meta-analysis (NMA) that combines direct head-to-head evidence and indirect comparative evidence [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%